Interaksi Umat Islam Indonesia Terhadap Lansia (Studi Living Qur’an) - Mohammad Rohmanan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Interaction of Indonesian Muslims towards the Elderly (Study of the Living Qur'an)Through the Qur'an and Hadith, Islam upholds the honor of the elderly. The attitudes, words, and deeds of the prophet Muhammad SAW were the actualization of the values of the Qur'an, so that he was dubbed "the walking Qur'an". Rasulullah SAW's exemplary example becomes the prototype of the concept of living al-Qur'an which is the values of Qur’an that are understood, and practiced collectively by Muslims community, then become local wisdom. This paper analyzes the elderly in the perspective of the living Qur’an of Indonesian Muslims. In processing the data in this study, the authors used thematic tafseer methods  and living quran. From this study the authors found that the concept of living quran Indonesian society in terms of treatment of the elderly is very good, it is manifested in some local wisdom of Indonesian society towards the elderly, such as the use of special language for the elderly, kissing the hands of the elderly, bowing when walking in front of the elderly and and the ritual of ziarah makam leluhur.